STEM Education and Research in a Changing World: Our Social Responsibility - Lucy Avraamidou (Journal of Research in Science, Mathematics and Technology Education, 2019)
At the awaking of the third millennium, in the here and now, the world finds itself facing a series of challenges, such as climate change, poverty, inequality, refugee crisis, unemployment, and so on, and so on. These global challenges raise a number of questions for STEM education and research: What should we teach our children? What knowledge and skills will our children need to have in 2050? How can we utilize scientific and technological knowledge to address global challenges? How can we think beyond the here and now in order to prepare ourselves for the future societies? Essentially, two questions are raised for STEM researchers: (a) what is the role of STEM education and research in a constantly changing world? and, (b) How does STEM shape our societies and how are our societies shaped by STEM?